2011
DOI: 10.1186/bcr2825
|View full text |Cite
|
Sign up to set email alerts
|

The prolyl hydroxylase enzymes are positively associated with hypoxia-inducible factor-1α and vascular endothelial growth factor in human breast cancer and alter in response to primary systemic treatment with epirubicin and tamoxifen

Abstract: IntroductionThe purpose of the present study was to investigate the relationship of expression of hypoxia inducible factor (HIF)-1α-modifying enzymes prolyl hydroxylase (PHD)1, PHD2 and PHD3 to response of tumours and survival in breast cancer patients enrolled in a phase II trial of neoadjuvant anthracycline and tamoxifen therapy.MethodsThe expression of PHD1, PHD2 and PHD3 together with HIF-1α and the HIF-inducible genes vascular endothelial cell growth factor (VEGF) and carbonic anhydrase IX were assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The study also alludes to the prognostic importance of oncogenic drivers on disease-specific survival. As targeted therapies directed against HIF1A and downstream targets emerge, [36][37][38] these observation may also have important therapeutic implications for identifying specific populations for screening and explaining treatment efficacy in familial male breast cancers.…”
Section: Resultsmentioning
confidence: 99%
“…The study also alludes to the prognostic importance of oncogenic drivers on disease-specific survival. As targeted therapies directed against HIF1A and downstream targets emerge, [36][37][38] these observation may also have important therapeutic implications for identifying specific populations for screening and explaining treatment efficacy in familial male breast cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Prolyl hydroxylases (PHD1, also known as EGLN2) is 1 of the 3 enzymes capable of hydroxylating the alpha subunit of HIF and results in polyubiquitinylation and proteasomal degradation of HIF (10). Several lines of evidence have indicated that EGLN2 is involved in development of multiple cancers (11)(12)(13)(14). Whether EGLN2 promotes or suppresses tumorigenesis depends on its cell and cancer type-specific expression (15).…”
Section: Introductionmentioning
confidence: 99%
“…This complexity reflects not only the crucial role of HIF1 in maintaining oxygen homeostasis but also the need to safeguard against its inappropriate activation. Previous reports have linked the PHD3-HIF and SUMOylation pathways with pathologies such as cancer and ischemia (Cheng et al, 2006;Chen et al, 2011;Flotho and Melchior, 2013;Fox et al, 2011;Loinard et al, 2009;Mo et al, 2005;Silveirinha et al, 2013;Su et al, 2010;Wang and Banerjee, 2004;Xue et al, 2010). In light of these findings, there is a great interest in the development of drugs targeting these pathways.…”
Section: Discussionmentioning
confidence: 99%